Intelligent coatings for corrosion control - Tiwari, Atul; Hihara, Lloyd H.; Rawlins, James Wayne (Amsterdam Elsevier, 2015)
Intelligent Coatings for Corrosion Control covers the most current and comprehensive information on the emerging field of intelligent coatings. The book begins with a fundamental discussion of corrosion and corrosion protection through coatings, setting the stage for deeper discussion of the various types of smart coatings currently in use and in development, outlining their methods of synthesis and characterization, and their applications in a variety of corrosion settings. Further chapters provide insight into the ongoing research, current trends, and technical challenges in this rapidly progressing field.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Corrosion and anti-corrosives.; Protective coatings; Electronic books